A numerical study on the effects of boot injection rate-shapes on the combustion and emissions of a kerosene-diesel fueled direct injection compression ignition engine. (1st September 2017) - Tay, Kun Lin; Yang, Wenming; Zhao, Feiyang; Yu, Wenbin; Mohan, Balaji
Highlights: Boot injection rate-shapes give lower nitrogen oxide emissions in general. Soot mass, particle number and size for kerosene combustion are lower than diesel. Lower boot injection velocity gives larger soot particles during initial combustion. High main injection velocity gives narrow soot mass distribution during late combustion. Abstract: In this work, the effects of boot injection rate-shapes on the combustion process and emissions formation of a direct injection compression ignition engine fueled with kerosene and diesel are investigated through numerical simulations. Boot injection rate-shapes with varying boot injection velocity and boot injection duration are used. The KIVA4-CHEMKIN code is used in conjunction with a phenomenological soot model and an improved kerosene-diesel reaction mechanism to study the combustion process and emissions formation. The phenomenological soot model consists of a number of sub-models from literature that accounts for soot particle inception, soot coagulation, soot surface growth via the hydrogen-abstraction-carbon-addition (HACA) mechanism and soot surface oxidation by oxygen (O2 ) and hydroxyl radical (OH). It should be noted that the improved kerosene-diesel reaction mechanism is robust enough to predict the combustion and emissions trends of kerosene with respect to diesel. From this study, boot injection rate-shapes are seen to cause combustion phasing and cause lower nitrogen oxide (NO) emissions in general. Furthermore, it is observed that when kerosene replaces diesel, engine efficiency and NO emissions increase while carbon monoxide (CO) and soot emissions decrease. Soot mass quantity, soot particle number and soot particle size are the lowest for pure kerosene combustion. Finally, detailed analyses of the effects of boot injection rate-shapes on soot particle dynamics are also presented.